Toponymic Area of the Moksha-Mordovian Blagodarovka Village of Borsky District of the Samara Region - Nikolay V. Belenov (Publishing house "Sreda", 2020)
The article is devoted to a comprehensive study of the toponymic area of the Moksha-Mordovian Blagodarovka village of the Borsky district of the Samara region. The aim of the article is an introduction into scientific discourse and the etymological analysis of toponymic vocabulary of the Blagodarovka village and its outskirts. The methods of the article are based on the principles of toponymic researches formulated in the works of leading Russian onomasticians. The article is based on the author's experience. As a result of the researches, the main characteristics and dialect belonging of the Blagodarovsky dialect of the Moksha-Mordovian language were determined, the geographical terminology existing in it was fixed, and the toponymic vocabulary was collected and analyzed. It is concluded that Blagodarovsky dialect of the Moksha-Mordovian language, despite a relatively short period of existence in the Russian environment with separation from other Mordovian language areas, is one of the most Russified Mordovian dialects of the Samara Volga region. A number of geographical names of the toponymic area of Blagodarovka find identical or close parallels in most other Moksha-Mordovian and Erzya-Mordovian toponymic areas of the region. The natural and geographical settlement conditions of native Blagodarovsky dialect speakers of the Moksha-Mordovian language as in the case of other Mordovian dialects of the Samara Volga region had a significant impact on the composition and semantics of the geographical terminology that exists in it.